Molecular characterisation of an Acinetobacter baumannii outbreak. Issue 2 (June 2020) - Al-Hassan, Leena L.; Al- Madboly, Lamiaa A.
Summary: Background: Acinetobacter baumannii are problematic hospital pathogens, and the increased incidence of multi drug resistance has significantly limited treatment options. The global epidemiology is not fully characterised due to large data gaps from low- and middle-income countries. This study characterised the molecular epidemiology of an A. baumanniii outbreak in Egypt. Methods: Fifty-four A. baumannii isolates were recovered from a 4-month-outbreak at Tanta University Hospitals (TUH). Associated clinical and demographic data, and the antibiograms were analysed, and Carbapenem resistant isolates were screened for acquired carbapenemase genes by PCR and sequencing. Epidemiological typing was performed by single-locus sequencing of bla OXA-51-like and Multi Locus Sequence Typing (MLST), and sequence types (STs) were analysed based on maximum-likelihood phylogeny (PhyML) to identify relatedness. Findings: Immune suppression and ICU admission were the most common co-morbidity and risk factor. Carbapenem resistance accounted for 81%, and correlated with the presence of OXA-23, NDM-1 and -2, and VIM-1 and -2 carbapenemases. Nine different bla OXA-51-like genes were identified which corresponded to 22 different Sequence Types (STs), including 10 novel. International clone (IC2) was the predominant clone. PhyML analysis revealed the presence of 2 distinct clones with multiple sub-lineages. Conclusion: Given the short duration of the study, there was a rare heterogeneous population in the hospital. Carbapenem resistance is mediated by acquired carbapenemases in diverse lineages indicating the possibility of horizontal gene transfer. The diversity indicates the influx of multiple lineages of IC2 into TUH from unknown sources. Molecular epidemiological studies are essential for infection prevention and control measures.